2017
DOI: 10.1145/3077618
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Misconceptions and Other Difficulties in Introductory Programming

Abstract: Efforts to improve computer science education are underway, and teachers of computer science are challenged in introductory programming courses to help learners develop their understanding of programming and computer science. Identifying and addressing students’ misconceptions is a key part of a computer science teacher's competence. However, relevant research on this topic is not as fully developed in the computer science education field as it is in mathematics and science education. In this article, we first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
199
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 390 publications
(264 citation statements)
references
References 109 publications
3
199
0
26
Order By: Relevance
“…Students are able to reason about surface features of a problem, but have difficulty envisioning the unknowns of given problems. In the area of program generation, research has shown that students have particular difficulty with conditionals and loops [18,21]. In general, educators need to be realistic about what can be accomplished within an introductory CS course.…”
Section: Computer Science Content In Ecsmentioning
confidence: 99%
“…Students are able to reason about surface features of a problem, but have difficulty envisioning the unknowns of given problems. In the area of program generation, research has shown that students have particular difficulty with conditionals and loops [18,21]. In general, educators need to be realistic about what can be accomplished within an introductory CS course.…”
Section: Computer Science Content In Ecsmentioning
confidence: 99%
“…Much literature about misconceptions in CSEd can be found: we list some of the most important causes of misconceptions, experienced especially by novices, divided into different areas, found mainly in (Clancy, 2004;Sirkiä, 2012;Sorva, 2013) and in the works they reference. For a complete review see for example (Qian and Lehman, 2017).…”
Section: Misconceptionsmentioning
confidence: 99%
“…The difficulties in learning programming were widely explored in past studies [24] [4], and Qian and Lehman [32] also reviewed the difficulties in learning programming. Some of the identified difficulties included designing solution plans, developing algorithms, syntactic mastery, writing and evaluating programmes, cognitive requirements, and limited programming ability.…”
Section: Introductionmentioning
confidence: 99%